The ‘Shellome’ of the Crocus Clam Tridacna crocea Emphasizes Essential Components of Mollusk Shell Biomineralization - Takeuchi, Takeshi; Fujie, Manabu; Koyanagi, Ryo; Plasseraud, Laurent; Ziegler-Devin, Isabelle; Brosse, Nicolas; Broussard, Cédric; Satoh, Noriyuki; Marin, Frédéric (Frontiers in genetics, 2021)
Molluscan shells are among the most fascinating research objects because of their diverse morphologies and textures. The formation of these delicate biomineralized structures is a matrix-mediated process. A question that arises is what are the essential components required to build these exoskeletons. In order to understand the molecular mechanisms of molluscan shell formation, it is crucial to identify organic macromolecules in different shells from diverse taxa. In the case of bivalves, however, taxon sampling in previous shell proteomics studies are focused predominantly on representatives of the class Pteriomorphia such as pearl oysters, edible oysters and mussels. In this study, we have characterized the shell organic matrix from the crocus clam, Tridacna crocea , (Heterodonta) using various biochemical techniques, including SDS-PAGE, FT-IR, monosaccharide analysis, and enzyme-linked lectin assay (ELLA). Furthermore, we have identified a number of shell matrix proteins (SMPs) using a comprehensive proteomics approach combined to RNA-seq. The biochemical studies confirmed the presence of proteins, polysaccharides, and sulfates in the T. crocea shell organic matrix. Proteomics analysis revealed that the majority of the T. crocea SMPs are novel and dissimilar to known SMPs identified from the other bivalve species. Meanwhile, the SMP repertoire of the crocus clam also includes proteins with conserved functional domains such as chitin-binding domain, VWA domain, and protease inhibitor domain. We also identified BMSP (Blue Mussel Shell Protein, originally reported from Mytilus ), which is widely distributed among molluscan shell matrix proteins. Tridacna SMPs also include low-complexity regions (LCRs) that are absent in the other molluscan genomes, indicating that these genes may have evolved in specific lineage. These results highlight the diversity of the organic molecules – in particular proteins – that are essential for molluscan shell formation.